Penggunaan Media Pembelajaran Online Selama Covid-19 dalam Pendidikan Jasmani Olahraga dan Kesehatan Sekolah Menengah Pertama Negeri Se-Kecamatan Darangdan - Asmira Rihani; Fahrudin Fahrudin; Muhammad Mury Syafei (Peneliti.net, 2021)
Indonesia and even the world is being hit by the spread of the corona virus or Corona Virus Disease 2019 (Covid-19). With the Covid-19 pandemic, the teaching and learning process (KBM) at SMPNs throughout the Darangdan District uses an online learning system. This study aims to determine the use of online learning media during covid-19 in physical education, sports and health at state junior high schools in the district of Darangdan. This research is quantitative descriptive. The method used in this study is a survey method, the data collection technique used is by making an online questionnaire using google form. the level of use of online learning media during covid-19 in physical education, sports and health at State Junior High Schools in the District of Darang and Purwakarta Regency was in the